2014
DOI: 10.1007/s11033-014-3747-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP3A4 and MDR1 gene (G2677T) polymorphisms on dose requirement of the cyclosporine in renal transplant Egyptian recipients

Abstract: Advances in immunosuppressive therapy allowed renal transplantation to become the treatment of choice for suitable candidates with (end stage renal disease) ESRD. The post-transplant therapeutic strategy is difficult due to narrow therapeutic indices for the currently used immunosuppressive drugs. Inter-individual differences in drug bioavailability are related to genetic and non genetic factors. The idea of targeted and personalized therapy is to achieve therapeutic success. The empirical dose has lost its va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…The allele frequencies of "G" and "A" of CYP3A4 rs4646437 were 76.3% (n = 380) and 23.7% (n = 118), respectively. The frequencies were significantly different from both Asians and Caucasians (Table 4) [11,18,19]. The CYP3A4*22 mutant allele was not found in this study.…”
Section: Resultscontrasting
confidence: 69%
“…The allele frequencies of "G" and "A" of CYP3A4 rs4646437 were 76.3% (n = 380) and 23.7% (n = 118), respectively. The frequencies were significantly different from both Asians and Caucasians (Table 4) [11,18,19]. The CYP3A4*22 mutant allele was not found in this study.…”
Section: Resultscontrasting
confidence: 69%
“…Similarly, a meta-analysis of studies showed no significant effect of the 3435C>T polymorphism on the pharmacokinetics of digoxin [88]. The literature data are summarized in Tables 2-4 [89][90][91][92][93].…”
Section: Biomarkersmentioning
confidence: 99%
“…As described above, ASV is eliminated primarily via CYP3A4-mediated oxidative metabolism [10,11]. rs4646437 is representative of CYP3A4 SNPs, and numerous studies have reported its relationship with drug metabolism and adverse events in the treatment for various diseases: adverse events caused by efavirenz in human immunodeficiency virus [23] and sunitinib in metastatic renal cell carcinoma [24]; finasteride exposure in prostate cancer risk [25]; immune responses to antiretroviral therapy in human immunodeficiency virus [26]; voriconazole exposure in invasive fungal infections [27]; tacrolimus metabolism among Chinese transplant recipients [28,29]; and cyclosporine kinetics in Egyptian and White transplant recipients [30,31]. Reportedly, rs4646437 influences the protein expression and enzymatic activity of hepatic CYP3A4 in a sex-dependent manner; females have higher expression/activity compared to males.…”
Section: Discussionmentioning
confidence: 99%